Comparison of diagnosing the relationship between the root of maxillary posterior tooth and maxillary sinus between panoramic radiography and cone beam computer tomography - SHU Jingjing; ZENG Feiyue; ZHANG Yanan; XU Qimei; TANG Jialu; XU Bin; SONG Liang (口腔疾病防治, 2021)
Objective To study the diagnostic accuracy and the distance between the root of maxillary posterior tooth and the maxillary sinus using panoramic radiography and cone beam computer tomography; to provide basic information for clinicians to treat diseases in the maxillary posterior region. Methods Eighty patients were included in this study. A total of 671 specimens were measured for the distance between the root tip and the maxillary sinus floor in both imaging modalities. Results The roots that did not contact the sinus floor or contacted but did not project into the sinus cavity showed an agreement of 82% and 70% when using panoramic radiography. Forty-eight percent of the roots that projected into the sinus cavity in panoramic radiography showed protrusion into the sinus with cone beam computer tomography (CBCT). For panoramic radiography and CBCT showing root projections into the sinus cavity, the average distances were 2.19 ± 1.82 mm and 1.47 ± 1.01 mm, respectively. There was a significant difference between the two values (P ＜ 0.05). Conclusion Panoramic radiography is more accurate when roots of maxillary posterior teeth do not contact the sinus floor or contact it. However, it has a lower accuracy rate when the tooth roots protrude into the sinus.